Pengaruh Media Online untuk Pengoptimalan Branding Guna Upgrading Market dalam UMKM Saung Farm Market - Pratama, Andreas Putra; S, Sugito (Yayasan Daarul Huda Kruengmane, 2023)
Saung Farm Market is an MSME that operates in the field of freshwater fish cultivation, the cultivation produced includes; tilapia, catfish, and other fish. This business uses a marketing model by opening a re-seller or commonly known as reselling fish that have been purchased from MSMEs and to buyers and customers from local residents only. However, in practice, MSME owners have obstacles, namely they are still embarrassed and hesitant to start marketing and lack the knowledge to use promotions in online media. Therefore, this research aims to provide training and educate the importance of promotions in online media to increase market share and market upgrading so that they are able to compete with other cultivators. The method used in working on this project is qualitative, the methods used in this method are going directly to obtain information by interviewing business actors and collecting data related to observations in the field. With this activity, business actors will indirectly be helped to spread their wings to develop a business.